Transformation of Christian Religious Education Learning in Jayapura: Conventional and Innovative Methods in the 21st Century Context - Kambu, Yosep; Rumbino, Daniel; Rumbiak, Mina; Kabanga, Lewi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The demands of the 21st century in the education world require adaptive and innovative learning. The implementation of Christian Religious Education (PAK) in Jayapura is accompanied by both conventional and unconventional, or innovative methods to support the effectiveness of learning. The aim of this research is to elaborate on the methods of PAK learning in Jayapura, Papua. The method used in this study is a qualitative descriptive method by applying literature review. Data were obtained through documentation techniques, involving downloading and documenting supporting data from books, research or journal papers, and proceedings from the last 10 years. The data were analyzed by classifying the effective application of learning methods. The results of this research indicate that the PAK learning methods applied in Jayapura, Papua, in terms of effectiveness, show that both conventional and unconventional methods are equally important in their implementation. Conventional methods tend to use techniques such as lectures, discussions, question and answer sessions, and assignments. While unconventional methods based on students' needs have not been optimally implemented in Jayapura